Integrating gender and social inclusion into Long-Term Low Emissions Strategies - Chevallier, Romy; Cramer, Laura; Huyer, Sophia (2025)
This info note highlights why integrating gender equality and social inclusion into Long Term Low-Emission Development Strategies (LT-LEDS) is essential for achieving climate resilient, low-carbon development. While LT-LEDS offer African countries a critical opportunity to align long-term climate ambition with inclusive economic transformation, gender considerations remain inconsistently applied. The note outlines progress, persistent gaps, and practical entry points for embedding gender across all stages of LT-LEDS including visioning, stakeholder engagement, policy design, financing, implementation, and monitoring. Drawing on African and global examples, it demonstrates how gender responsive and gender-transformative approaches strengthen the effectiveness, equity and legitimacy of climate strategies. It concludes with recommendations for governments and partners to ensure LT-LEDS deliver socially just and climate-ambitious outcomes.